Can urodynamics distinguish between urethral strictures and Benign Prostatic Hyperplasia (BPH)?. (July 2015) - Bishara, Samuel; Foley, Charlotte; Peters, John; Philp, Tim; Malone-Lee, James
Objectives: We tested whether pressure flow studies could distinguish between patients with Benign Prostatic Hyperplasia (BPH) and urethral strictures and hypothesised that urethral strictures were associated with a lower closure pressure and increased slope of the passive urethral relation compared to benign prostatic obstruction. Patients and method: Ninety patients who had Transurethral Resection of Prostate (TURP) and 45 male patients who had an optical urethrotomy or urethral dilatation for urethral stricture disease, who had a prior urodynamics study, were evaluated. Results: Patients with urethral stricture disease had lower closure pressures than those undergoing TURP (22.07 vs. 28.4 cmH2 O, p =0.0039, r =0.61). However, the slope of the passive urethral relation was indistinguishable between the two groups. Only 60% of patients with symptomatic urethral strictures were categorised as unequivocally obstructed by the Abrams-Griffiths nomogram. Conclusion: Urethral strictures are associated with lower closure pressures than prostatic obstruction; however, there was no difference in the urethral resistance relation.